COVID-19 Infection in Peritoneal Dialysis Patients: A Comparative Outcome Study with Patients on Hemodialysis and Patients without Kidney Disease - KAZANCIOĞLU, RÜMEYZA; KAZANCIOĞLU, Rümeyza; GÜRSU, MELTEM; Ozturk, Savas; TURGUTALP, KENAN; GÜRSU, Meltem; ARICI, MUSTAFA; ORUÇ, AYŞEGÜL; Ahbap, Elbis; GÖKÇAY BEK, SİBEL; Sengul, Erkan; Ogutmen, Melike Betul; et al. (My University, 2022)
Objectives: There is limited data about coronavirus disease-19 (COVID-19) characteristics and results in peritoneal dialysis (PD) patients. This study aimed to investigate the characteristics and outcomes among PD patients and compare them with matched hemodialysis (HD) patients and a control group without kidney disease. Methods: We included 18 PD patients and consecutive age- and gender-matched 18 HD and 18 patients without kidney disease (control group) registered into the Turkish Society of Nephrology database including 1301 COVID-19 patients. We compared demographic, clinical, radiological, laboratory data, and outcomes namely intensive care unit (ICU) admission, mechanical ventilation, mortality, and composite outcome (death and/or ICU admission). Results: ICU admission, mechanical ventilation, and mortality rates in PD patients (27.8%, 22.2%, and 22.2%, respectively) and the HD group (16.7%, 11.1%, and 16.7%, respectively) were higher than the control group (11.1%, 11.1%, and 5.6%, respectively), but intergroup comparison did not reveal difference. A total of 11 (20.3%) patients had composite outcome (6 PD patients, 3 HD patients, and 2 patients in the control group). In Cox regression analysis, higher age and higher CRP level were related to increased risk of composite outcome. Adjusted rate of composite outcome in PD group was significantly higher than the control group (P =.050). This rate was similar in HD and control groups (P =.30). Conclusions: Combined in-hospital mortality and/or ICU admission of PD patients with COVID-19 was significantly higher than the control patients. There is a need for careful surveillance of PD patients for infection signs and prompt treatment of COVID-19.
Keywords: COVID-19; peritoneal dialysis; hemodialysis; outcome